Form of Classic Dangdut Music Performance The "Bintang Remaja" Dangdut Music Group In Kendal Regency - Uliyana, Eliya; Moh. Muttaqin (Jurnal Seni Musik, 2024)
Dangdut music is highly popular among the general public. This study aimed to identify, analyze, and describe the forms of performance by the Bintang Remaja classic dangdut music group in Kendal regency. This study employed descriptive qualitative method. Data were collected using observation, interviews, and documentation. The validity of the data was ensured through triangulation techniques. Data analysis was conducted in stages, including data reduction, data presentation, and drawing conclusions. The results of the study reveal two aspects of the Bintang Remaja dangdut music group’s performance: composition and presentation: (1) The composition aspect includes rhythm in a 4/4 time signature; melody utilizing three movements (horizontal, stepwise, and leaps); harmony with chord progressions I, VII, V, VI; tempo in the Allegro category; dynamics, expression, and instruments such as microphone, guitar, bass, keyboard, flute, drums, and kendang; with song lyrics for "Teman Biasa." (2) The presentation aspect encompasses stage setup with outdoor rigging; sound system using the Ashley brand; lighting with PAR LED and Moving Head Beam; costumes and makeup; performance structure including opening, main performance, and closing; and formation. In addition, the Bintang Remaja music group consistently performs works by Rhoma Irama and other classic dangdut artists, as the group is known for its characteristic rendition of classic dangdut music.